Asthma Self-Management Practices among Patients with Asthma at Chuka County Referral Hospital (CCRH), Kenya - Micheni, Hellen; Gitonga, Lucy; Gichobi, Beth; Kainga, Stephen; Micheni, Purity (Journal of Health, Medicine and Nursing, 2025)
Purpose: Asthma is a global public health problem that affects people of all ages contributing significantly to morbidity and mortality.It is a chronic inflammatory disease of the respiratory tract. This study aimed at assessing self-management practices for asthma control among adult patients with asthma. Methodology: The study adopted a descriptive cross-sectional survey design. A sample size of 118 patients was obtained using Fisher’s et al formula and the sample was selected using simple random sampling. A researcher administered questionnaire was used to collect data. Data was analyzed using statistical package for social sciences version 26 to generate frequencies, mean and measures of central tendency. Pearson’s correlation coefficient was used to determine the relationship between self-management practices and asthma control. Findings: The study concluded that there is a negative correlation between self- management practices and Frequency of Asthma Control, r = -0.190 with a significance p-value = 0.045. This implies that frequency of asthma symptoms and practice of trigger identification and control are statistically significant at 0.05 level (2-tailed). Key facilitators of asthma self-management practices include; effective communication with healthcare workers, availability and affordability of medications in government hospitals. Some of the reported barriers to asthma self-management include presence of comorbidities, poor self-control and lack of knowledge on ASM. Unique Contribution to Theory, Practice and Policy: This study recommends implementation of outreach programs in the community to increase awareness about asthma and associated self-management essentials.